Dampak Program Pengembangan Karir dan Pelatihan terhadap Loyalitas Karyawan pada Perusahaan Retail di Kota Palopo - Nur Pertiwi; Indra Kusdarianto; Antong Antong (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to examine the effect of career development programs and training on employee loyalty in retail companies in Palopo City. The background of this research is the high turnover rate in the retail sector, which can disrupt productivity and service quality. The study employed a descriptive quantitative method with a population of 325 Hypermart employees and a sample of 76 respondents selected through purposive sampling. Data were analyzed using multiple linear regression. The results show that career development has a significant effect on employee loyalty, training has a significant effect on loyalty, and both simultaneously have a significant effect. In conclusion, career development and training programs effectively enhance employee loyalty. The novelty of this research lies in its focus on the retail industry in Palopo City, which remains underexplored, thereby contributing new empirical insights into employee loyalty in regional retail sectors.